The significance and benefits of heritage area conservation program towards tourism industry / Fatin Atiqah Abu Othman - Abu Othman, Fatin Atiqah (2006)
Melaka “the end of monsoons and the beginning of others”, is Malaysia’s as historic city and the land of the legendary Malay warriors, Hang Tuah and Hang Jebat. Melaka or Malacca is where the history of Malaysia unfolds: the birth of the Malay Sultanate, the coming of the first colonial powers, the Portuguese and the Dutch to the Malay peninsular, and later years, the town where the independence of our fair Nation was first announced. The blend of ancient and modern history and culture of temples and mosques, kampungs and narrow streets, sea, river and hills, is what Melaka unique. Preserving this historical cultural and architectural heritage becomes the responsibility of every Malaysian. Every piece of mankind in this world has its own legacy. Every steps and every breath in human kind has its own story and this is the things that create heritage. Heritage buildings are the architectural legacy of making regardless of its style of cultural influence. Imagining our town and cities including our countryside without old buildings as we tend to take them for granted and overlook their importance. Generally, ‘conservation’ implies change, but change for the better (e.g. to provide better economic re-use of existing building stock) in controlled ways.lt also brings the meaning maintaining work which is to returning the monument and historical site to a similar origin. Conservation in many places has a bad name. It is seen, quite often erroneously, as a block to progress and development. Conservation is perceived by many as the province of the few, as a select exercise affordable only to the wealthy or middle classes and at the other end of the spectrum to progress and development. This is where tourism comes in as the major way in many situations, that society - communities both large and small - can use conservation to keep what is good and keep out what is bad. Tourism is the best indicator today in this area of endeavor as it becomes more and more community dependent activity. Therefore, regarding this, I would like to identify the significance and benefits of heritage area conservation towards tourism industry. The content of this study is to identify the significance and the benefits that could be derived from the relationship of heritage area conservation to the tourism industry. Subsequently, the study will focus on heritage area in Bandar Hilir, Melaka as tourism destination. Furthermore, it will derived the impact of the conservation program that had been carried out in the heritage area towards the tourism industry. From the case study, questionnaire distribution will be made to the local people in the area and the tourist. The analysis will be made to study the outcome of the questionnaire to identify the impact from the consequences of tourist coming to the heritage area. Finally, recommendations were made based on the conclusion of the findings. Several aspects in order to improve the conservation would be considered, This is to ensure that the conservation program will be definitely give benefits to the local residents and tourism industry.